Retroperitoneal Abscess Formation as a Result of Spilled Gallstones during Laparoscopic Cholecystectomy: An Unusual Case Report - Grigoris Chatzimavroudis; Stefanos Atmatzidis; Basilis Papaziogas; Ioannis Galanis; Ioannis Koutelidakis; Triantafyllos Doulias; Petros Christopoulos; George Papadakis; Konstantinos Atmatzidis; John Makris (Case Reports in Surgery)
One of the complications of laparoscopic cholecystectomy for gallstone disease that seems to exceed that of the traditional open method is the gallbladder perforation and gallstone spillage. Its incidence can occur in up to 40% of patients, and in most cases its course is uneventful. However in few cases an abdominal abscess can develop, which may lead to significant morbidity. Rarely an abscess formation due to spilled and lost gallstones may occur in the retroperitoneal space. We herein report the case of a female patient who presented with clinical symptoms of sepsis six months following laparoscopic cholecystectomy. Imaging investigations revealed the presence of a retroperitoneal abscess due to retained gallstones. Due to patient’s decision to refuse abscess’s surgical drainage, she underwent CT-guided drainage. The 24-month followup of the patient has been uneventful, and the patient remains in good general condition.